2017
DOI: 10.1155/2017/2824615
|View full text |Cite
|
Sign up to set email alerts
|

Association between Scale-Free Brain Dynamics and Behavioral Performance: Functional MRI Study in Resting State and Face Processing Task

Abstract: The scale-free dynamics of human brain activity, characterized by an elaborate temporal structure with scale-free properties, can be quantified using the power-law exponent (PLE) as an index. Power laws are well documented in nature in general, particularly in the brain. Some previous fMRI studies have demonstrated a lower PLE during cognitive-task-evoked activity than during resting state activity. However, PLE modulation during cognitive-task-evoked activity and its relationship with an associated behavior r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…The mid‐frequency oscillatory sine wave of 0.18 Hz caused a minor impact on the model. Finally, the high‐frequency sine wave of 0.45 Hz decreased the slope of the PLE and increased the MF, consistent with the shorter ITI of other studies (He et al, 2010 ; Kasagi et al, 2017 ; Lin et al, 2016 ). We used Pearson's correlation for the PLE (r‐values are shown in Figure 7 ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The mid‐frequency oscillatory sine wave of 0.18 Hz caused a minor impact on the model. Finally, the high‐frequency sine wave of 0.45 Hz decreased the slope of the PLE and increased the MF, consistent with the shorter ITI of other studies (He et al, 2010 ; Kasagi et al, 2017 ; Lin et al, 2016 ). We used Pearson's correlation for the PLE (r‐values are shown in Figure 7 ).…”
Section: Resultssupporting
confidence: 88%
“…The PLE increase in task states represents a surprising finding since previous EEG, MEG, ECoG (He et al, 2010 ; Lin et al, 2016 ), and fMRI (He et al, 2010 ; Kasagi et al, 2017 ) often observed PLE decreases in relatively fast event‐related and block task designs. Conversely, our fMRI analysis with atypically long ITI found substantial PLE increases in task states across the cerebral cortex in two core‐periphery topographies (SCP and JCP) in the primary and replication datasets.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The potential relationship between cortical criticality and optimal anticipatory oscillation is presented in Figure 4. The theorized value of allostatic state criticality is further highlighted through depiction that the relationship between criticality and optimal anticipatory oscillation may be non-linear, given that as with other complex systems, many functions of the brain are likely to operate on the basis of power laws (e.g., Thiel, 2014; Bettinger, 2017; Kasagi et al, 2017).…”
Section: The Paradigm Of Allostatic Orchestration (Pao)mentioning
confidence: 99%